2017
DOI: 10.1007/s00247-017-3827-8
|View full text |Cite|
|
Sign up to set email alerts
|

Community-acquired pneumonia in children — a changing spectrum of disease

Abstract: Pneumonia remains the leading cause of death in children outside the neonatal period, despite advances in prevention and management. Over the last 20 years, there has been a substantial decrease in the incidence of childhood pneumonia and pneumonia-associated mortality. New conjugate vaccines against Haemophilus influenzae type b and Streptococcus pneumoniae have contributed to decreases in radiologic, clinical and complicated pneumonia cases and have reduced hospitalization and mortality. The importance of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 79 publications
0
91
0
13
Order By: Relevance
“…In the Drakenstein Child Health Study in Africa, where pneumococcal vaccination is included in their national immunization programme, they found a strong association between RSV, B. pertussis and H. influenzae with pneumonia, and that H. Influenzae occurred most frequently [25]. In a review article by Zar et al, the authors highlighted the changing disease spectrum of pneumonia in childhood, particularly the reducing prevalence of S. pneumoniae and Hib amid widespread use of vaccination [39]. In a large prospective study in India, S. aureus was detected in about 7% of children admitted with a LRTI.…”
Section: Discussionmentioning
confidence: 99%
“…In the Drakenstein Child Health Study in Africa, where pneumococcal vaccination is included in their national immunization programme, they found a strong association between RSV, B. pertussis and H. influenzae with pneumonia, and that H. Influenzae occurred most frequently [25]. In a review article by Zar et al, the authors highlighted the changing disease spectrum of pneumonia in childhood, particularly the reducing prevalence of S. pneumoniae and Hib amid widespread use of vaccination [39]. In a large prospective study in India, S. aureus was detected in about 7% of children admitted with a LRTI.…”
Section: Discussionmentioning
confidence: 99%
“…Current case management guidelines maximize diagnostic sensitivity over specificity, potentially resulting in antibiotic overuse. 16 Existing research suggests that most fast-breathing pneumonia cases will resolve without antibiotic therapy. In a study evaluating fever etiology among outpatient children in Tanzania, the authors found that, in the absence of critical illness and malaria, most febrile children could be treated supportively without antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…[54,55] In the current era of conjugate vaccines targeting Haemophilus influenzae type b (Hib) and Streptococcus pneumoniae, there has been a shift in the spectrum of pathogens causing pneumonia, with viruses contributing to a greater proportion of severe LRTI episodes (evidence level Ib) and non-typable H. influenzae and S. aureus emerging as important bacterial pathogens. [48,49,[56][57][58][59][60]…”
Section: Aetiology Diagnosismentioning
confidence: 99%